Exploring the Translation Patterns of “Ren”: Insights into Translation Practice from a Cross-Cultural Perspective - Yang, Dan (International Research in Education, 2024)
The concept of rén is a central aspect of traditional Chinese political thought, with various translations in English literature. This study examines the translations of rén in Lectures on Traditional China’s Political Thoughts and analyzes the statistics and trends among these translations. The findings reveal a lack of uniformity in the translations of rén, indicating that different translators interpret the concept in various ways. Furthermore, the parts of speech used in the translations differ, reflecting the unique perspectives of local and overseas scholars. Through etymological interpretations, this study explores the meanings behind typical English translations of rén such as virtue, benevolent, morality, humanity, good, kind, love, compassion, authoritative, man of skill, perfect man, and gentleness. These interpretations shed light on the diverse understanding of rén in traditional Chinese political thought. Overall, this study provides a comprehensive overview of the translations and interpretations of rén, highlighting the complexity and richness of this fundamental concept in Chinese philosophy.